Management strategy to avoid chytrid fungus infection in egg clutches of the Valcheta frog Pleurodema somuncurense - Arellano, Maria Luz (2018)
Eggs which were removed from a chytrid- infected population of Valcheta frogs shortly after laying and then hatched in a clean environment resulted in juveniles free of the fungus.